Argon Plasma Treatment to Tune Perovskite Surface Composition for High Efficiency Solar Cells and Fast Photodetectors. Issue 9 (10th January 2018) - Xiao, Xun; Bao, Chunxiong; Fang, Yanjun; Dai, Jun; Ecker, Benjamin R.; Wang, Congcong; Lin, Yuze; Tang, Shi; Liu, Ye; Deng, Yehao; Zheng, Xiaopeng; Gao, Yongli; et al.
Abstract: The surface composition of perovskite films is very sensitive to film processing and can deviate from the optimal, which generates unfavorable defects and results in efficiency loss in solar cells and slow response speed in photodetectors. An argon plasma treatment is introduced to modify the surface composition by tuning the ratio of organic and inorganic components as well as defect type before deposition of the passivating layer. It can efficiently enhance the charge collection across the perovskite–electrode interface by suppressing charge recombination. Therefore, perovskite solar cells with argon plasma treatment yield enhanced efficiency to 20.4% and perovskite photodetectors can reach their fastest respond speed, which is solely limited by the carrier mobility. Abstract : An argon plasma treatment is introduced to modify the surface trap types of halide perovskite, which improves the efficiency of a solar cell to 20.4%. The plasma treatment is shown as being also applicable to modify the perovskite single crystals, which enable the fastest response speed for single‐crystal photodetectors.